Outcomes with the Boston Type 1 Keratoprosthesis at Instituto de Microcirugía Ocular IMO - Güell, Jose L. (Elsevier, 2011)
PURPOSE: To report the outcomes on the Boston Type 1 Keratoprosthesis at our institution. DESIGN: Retrospective analysis case series. PARTICIPANTS: We analyzed 54 eyes of 53 patients who previously underwent Boston Type 1 Keratoprosthesis surgery at our institution from July 2006 to March 2011. METHODS: Preoperative and postoperative parameters were collected and analyzed. MAIN OUTCOME MEASURES: Visual acuity and keratoprosthesis stability. RESULTS: Common preoperative diagnoses were penetrating keratoplasty failure in 49 eyes (90.7%), chronic keratitis in 2 eyes (3.7%), ocular cicatricial pemphigoid in 1 eye (1.85%), Stevens Johnson syndrome in 1 eye (1.85%) and corneal vascularization in 1 eye (1.85%). Additionally, 40 eyes (74%) had preoperative glaucoma, and an Ahmed valve was implanted in 55% of them. Preoperative BCVA ranged from 20/200 to light perception. At an average follow-up of 20.15 months ± 12.7 (range, 1–56), postoperative vision improved to ⩾20/200 in 18 eyes (33.3%) and ⩾20/50 in 4 eyes (7.4%). The graft retention was 96%. CONCLUSIONS: The Boston Type 1 keratoprosthesis is a valid option for high-risk patients. The design improvements in the Boston keratoprosthesis, as well as the daily implementation of the therapeutic methods, have notably diminished occurrence of the most serious complications, such as corneal necrosis and endophthalmitis. As such, glaucoma and its subsequent complications now stand as the most prevalent prognostic factor in the long term.